Catalpol reduced LPS induced BV2 immunoreactivity through NF-κB/NLRP3 pathways: an in Vitro and in silico study - She, Yong; Shao, Chong-yu; Liu, Yuan-feng; Huang, Ying; Yang, Jiehong; Wan, Hai-tong (Frontiers in Pharmacology, 2024)
Ischemic Stroke (IS) stands as one of the primary cerebrovascular diseases profoundly linked with inflammation. In the context of neuroinflammation, an excessive activation of microglia has been observed. Consequently, regulating microglial activation emerges as a vital target for neuroinflammation treatment. Catalpol, a natural compound known for its anti-inflammatory properties, holds promise in this regard. However, its potential to modulate neuroinflammatory responses in the brain, especially on microglial cells, requires comprehensive exploration. In our study, we investigated into the potential anti-inflammatory effects of catalpol using lipopolysaccharide (LPS)-stimulated BV2 microglial cells as an experimental model. Our results revealed that catalpol effectively suppressed the production of nitric oxide (NO) induced by LPS and reduced the expression of microglial cell activation markers, including Iba-1. Furthermore, we observed that catalpol downregulated the mRNA expression of pro-inflammatory cytokines such as IL-6, TNF-α, and IL-1β, as well as key molecules involved in the NLRP3 inflammasome and NF-κB pathway, including NLRP3, NF-κB, caspase-1, and ASC. Our mechanistic investigations shed light on how catalpol operates against neuroinflammation. It was evident that catalpol significantly inhibited the phosphorylation of NF-κB and NLRP3 inflammasome activation, both of which serve as upstream regulators of the inflammatory cascade. Furthermore, by employing molecular docking and molecular dynamics simulation (MDs), we explored the binding affinity of catalpol to key targets, such as NF-κB, NLRP3, and IL-1β which all showed strong binding interactions. In conclusion, our findings support the idea that catalpol holds the potential to alleviate neuroinflammation, and it is achieved by inhibiting the activation of NLRP3 inflammasome and NF-κB, ultimately leading to the downregulation of pro-inflammatory cytokines. Catalpol emerges as a promising candidate for the treatment of neuroinflammatory conditions.